ZmG6PDH1 in glucose-6-phosphate dehydrogenase family enhances cold stress tolerance in maize - Li, Xin; Cai, Quan; Yu, Tao; Li, Shujun; Li, Sinan; Li, Yunlong; Sun, Yan; Ren, Honglei; Zhang, Jiajia; Zhao, Ying; Zhang, Jianguo; Zuo, Yuhu (Frontiers in Plant Science, 2023)
Glucose-6-phosphate dehydrogenase (G6PDH) is a key enzyme in the pentose phosphate pathway responsible for the generation of nicotinamide adenine dinucleotide phosphate (NADPH), thereby playing a central role in facilitating cellular responses to stress and maintaining redox homeostasis. This study aimed to characterize five G6PDH gene family members in maize. The classification of these ZmG6PDHs into plastidic and cytosolic isoforms was enabled by phylogenetic and transit peptide predictive analyses and confirmed by subcellular localization imaging analyses using maize mesophyll protoplasts. These ZmG6PDH genes exhibited distinctive expression patterns across tissues and developmental stages. Exposure to stressors, including cold, osmotic stress, salinity, and alkaline conditions, also significantly affected the expression and activity of the ZmG6PDHs, with particularly high expression of a cytosolic isoform (ZmG6PDH1) in response to cold stress and closely correlated with G6PDH enzymatic activity, suggesting that it may play a central role in shaping responses to cold conditions. CRISPR/Cas9-mediated knockout of ZmG6PDH1 on the B73 background led to enhanced cold stress sensitivity. Significant changes in the redox status of the NADPH, ascorbic acid (ASA), and glutathione (GSH) pools were observed after exposure of the zmg6pdh1 mutants to cold stress, with this disrupted redox balance contributing to increased production of reactive oxygen species and resultant cellular damage and death. Overall, these results highlight the importance of cytosolic ZmG6PDH1 in supporting maize resistance to cold stress, at least in part by producing NADPH that can be used by the ASA-GSH cycle to mitigate cold-induced oxidative damage.